Implementation of Principal's Communication Management in Improving Teacher Performance - Dini Tricahyati; Al Muhajir (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2026)
This study aims to examine the implementation of communication management, communication strategies, supporting factors and communication barriers of school principals in improving teacher performance at SMK Negeri 2 Lhokseumawe. The research uses a qualitative approach with a descriptive type of research. Data were collected through semi-structured interviews with principals and teachers, participatory observations, and documentation studies. Data analysis was carried out thematically by grouping based on communication indicators, strategies applied, and supporting and inhibiting factors. The results of the study show that the implementation of communication management of school principals is carried out through the delivery of clear and structured information, routine supervision, and open communication between principals and teachers. Communication strategies implemented include the use of various communication channels, providing constructive feedback, and a personalized approach to increase teacher motivation and engagement. The main supporting factors include information openness, effective communication channels, and motivational support from the principal, while the inhibiting factors include teachers' psychological barriers, unclear messages, and differences in perception that can reduce the effectiveness of communication. The implications of this study emphasize the importance of implementing systematic, adaptive, and participatory communication management to create a conducive work environment, improve teacher professionalism, and improve the quality of learning continuously